2017
DOI: 10.1093/protein/gzx023
|View full text |Cite
|
Sign up to set email alerts
|

Insights from engineering the Affibody-Fc interaction with a computational-experimental method

Abstract: The interaction between the Staphylococcal Protein A (SpA) domain B (the basis of the Affibody) molecule and the Fc of IgG is key to the use of Affibodies in affinity chromatography and in potential therapies against certain inflammatory diseases. Despite its importance and four-decade history, to our knowledge this interaction has never been affinity matured. We elucidate reasons why single-substitutions in the SpA which improve affinity to Fc may be very rare, and also discover substitutions which potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As an illustration of this, recent benchmarking on a large blind subset of the recently released SKEMPI 2.0 (487 mutations in 56 complexes), which none of the predictors had previously seen, showed that iSEE, FoldX, mCSM, and BindProfX did not perform as well as on the training sets they originally used with PCC values all below 0.4. Even so, we have seen some promising contributions of such predictors to practical problems, for example, References .…”
Section: Discussionmentioning
confidence: 99%
“…As an illustration of this, recent benchmarking on a large blind subset of the recently released SKEMPI 2.0 (487 mutations in 56 complexes), which none of the predictors had previously seen, showed that iSEE, FoldX, mCSM, and BindProfX did not perform as well as on the training sets they originally used with PCC values all below 0.4. Even so, we have seen some promising contributions of such predictors to practical problems, for example, References .…”
Section: Discussionmentioning
confidence: 99%
“…Many mass-increasing mutations were selected by our method, while only the mass-decreasing mutations yielded near-WT affinities, thus FoldX appears not to get this balance right in the context of helices in the PPI core (Levy, 2010). In prior work we found near-WT affinities even with increases in molecular mass (Nosrati et al, 2017), but these were on the PPI rim (Levy, 2010), where there is more space available. Thus in future application of this method for that goal, it may be beneficial to explicitly select mass-or volume-decreasing substitutions for any positions in the core and on secondary-structural elements.…”
Section: Discussionmentioning
confidence: 80%
“…Many mass-increasing mutations were selected by our method, while only the mass-decreasing mutations yielded near-WT affinities, thus FoldX appears not to get this balance right in the context of helices in the PPI core [ 23 ]. In prior work we found near-WT affinities even with increases in molecular mass [ 24 ], but these were on the PPI rim [ 23 ], where there is more space available. Thus in future application of this method for that goal, one may consider preferring mass- or volume-decreasing substitutions for any positions in the core and on secondary-structural elements.…”
Section: Discussionmentioning
confidence: 98%